GREEN BOOK MOVIE: PORTRAYAL OF RACISM IN AMERICA - Wardana, Irvan; Weda, Sukardi; Affandi, Akhmad (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
In the current century, racism is a problem in society that is still happening. Various kinds of movements have been made so that this action can be completely destroyed. The art activists began to run campaigns through their literary works. One of them is the movie called Green Book. Taking the green book film as the object of research, this research wants to show acts of racism in movie and compare acts of racism that occur against black people in the United States. This movie is based on the true story of American society during the Jim Crow Act in 1962. The author uses a qualitative descriptive method with a sociological approach to explain racist behavior to black Americans in America. The results of this study indicate that the racist behavior that occurs in the movie